Exploratory Factors Analysis for Accommodation Selection on Khao San Road, Bangkok - Srichada, Tuaenjai; Seanyen, Taksina; Hasoh, Apapohn (Rajapark Journal, 2022)
The objective of this research was to study the confirmed factors affecting the selection of accommodation in Khao San Road in Bangkok. The sample group consisted of 138 Thai tourists, collected by accidental sampling and using questionnaires with confidence according to the Cronbach's alpha coefficient formula of 0.85. The data were analyzed using the components by means of extraction of the core components, rotating axes, and orthogonal elements with the varimax method. It was found that the factors affecting accommodation selection in Khao San Road in Bangkok consist of 3 main components and 12 sub-elements with a total variance of 60.112%, each of which describes 18.400% variance 11.874%, 11.371%, 9.781%, and 8.687%, respectively. It was found that the first elements of service and security had the highest variance percentage. It was signified that most of the choices of accommodation in Khao San Road in Bangkok.